Influence of sucrose on the stability of W1/O/W2 double emulsion droplets. Issue 101 (30th September 2015) - Li, Jie; Su, Lin; Li, Jing; Liu, Mei-Fang; Chen, Su-Fen; Li, Bo; Zhang, Zhan-Wen; Liu, Yi-Yang
Abstract : Number of emulsion particles vs. time with various sucrose (Suc) concentration in rotating flow field. (Large sized W1/O/W2 double emulsion droplets with uniform wall thickness and diameters were prepared by adopting the emulsion microencapsulation method.) Abstract : Large sized W1/O/W2 double emulsion droplets with uniform wall thickness and diameters were prepared by adopting the emulsion microencapsulation method. Via visually online counting the number of double emulsion droplets over observing time, the stability of these compound droplets solidified in a constant rotating flow field was comprehensively studied. Combining emulsion kinetics, the adsorption radius of polymer chains, surface tension and rheological properties of the outer water phase (W2), the influence of sucrose concentration on the stability of double emulsion droplets was systematically investigated. Combining the change of surface tension, the size of adsorbed polyvinyl alcohol (PVA) chains and storage modulus of the W2 phase, mechanisms of the interactions between sucrose molecules and PVA chains were fully elucidated in this paper. Moreover, the results showed that the stability of the double emulsion droplets was improved when the contents of sucrose was less than 1.0 wt%. This is probably due to the proper match between shear force and surface tension of the W2 phase, and less inward force caused by osmotic pressure in dilute sucrose concentrations.